2021
DOI: 10.1016/j.amsu.2021.102562
|View full text |Cite
|
Sign up to set email alerts
|

Lethargy as an initial symptom of intussusception secondary to Meckel's diverticulum in a 2.5 year-old girl: Case report

Abstract: Introduction and importance: Intussusception is one of the most common causes of acute abdomen and surgical morbidities in the childhood. In a paediatric presentation of intussusception due to Meckel's diverticulum there may be acute onset of abdominal pain, vomiting or painless red currant stools. However, Lethargy has been described as a rare presenting symptom Case presentation We present a case of 2,5 – year old female complained of acute alternation in consciousnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The clinical manifestations of intussusception in children are varied and non-specific ( 11 13 ). The classic triad of pediatric intussusception includes vomiting, intermittent abdominal pain, and bloody currant jelly stool; however, this occurs in fewer than half of affected patients ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of intussusception in children are varied and non-specific ( 11 13 ). The classic triad of pediatric intussusception includes vomiting, intermittent abdominal pain, and bloody currant jelly stool; however, this occurs in fewer than half of affected patients ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although in the literature, children up to 10 years of age represent more than 50% of symptomatic MD cases, ( 3 ) the incidence in the reports reviewed in this discussion proved to be slightly different. Two patients were less than 6 months of age, ( 6 , 10 ) three between 1 and 6 years of age, ( 14 , 16 , 17 ) five between 15 and 30 years of age ( 5 , 7 , 13 , 18 , 19 ) and five between 40 and 50 years of age. ( 8 , 9 , 11 , 12 , 15 )…”
Section: Discussionmentioning
confidence: 99%
“…From a geographical perspective, we observed that 15 publications came from five continents. One was from America (United States), (5) four from Europe (Italy, (6) France, (7) Spain (8) and the United Kingdom), (9) one from Africa (Tunisia), (10) seven from Asia (Japan, (11)(12)(13)(14) South Korea, (15) China (16) and Syria) (17) and two from Oceania (Australia). (18,19) Regarding the age of the patients included in this sample, there was a range from newborns to 49 years of age.…”
Section: Epidemiologymentioning
confidence: 99%
“…In general, most intussusceptions can be categorized as primary or idiopathic, with thickened bowel wall lymphoid tissue (Peyer patches) acting as the lead point. Approximately 5–12% of intussusceptions are pathological, which usually present with different symptoms and are caused by conditions such as Meckel’s diverticula ( 4 ), intestinal polyps ( 5 , 6 ), intestinal duplication ( 7 ), allergic purpura ( 8 ) and some rare digestive tract malignant tumors ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%